PEMBENTUKAN KEMANDIRIAN BERBISNIS REMAJA MASJID MELALUI USAHA KEMITRAAN DI KECAMATAN NGRONGGOT KAB. NGANJUK - Badrus; Mohammad Auza’i Aqib Aqib; Naila Asnal Mala; Moh. Muntahal Firdaus (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2026)
This community service is focused on the formation of business independence through youth mosque business partnerships in Ngronggot District. This mentoring uses a participatory action research (PAR) approach. The results of the mentoring show that, the formation of business independence begins with increasing business administration skills, as a basic satisfaction that needs to be mastered by youth mosques in starting a business, increasing the economic business of youth mosques can be developed through several ways, including by providing motivation and joint coaching and providing facilities and cooperation in managing economic businesses, increasing the business independence of youth mosques through MSMEs business partnerships can be done by mutually understanding mutual agreements, so that there will be mutual synergy and benefit from both parties